(untitled) (Research, Society and Development, 2022)
This study aimed to identify the main aspects of the systematization of nursing care in rooming-in based on recording instruments. An integrative review of the literature of the last 10 years was carried out through an electronic search in the following databases: SCIELO, LILACS, BDENF and Medline, available at the Virtual Health Library. The results point to the importance and benefits of the systematic record of nursing care and of standardized instruments in terms of improving the work process in order to promote humanized and qualified care in the face of the needs of postpartum women and newborns. The main difficulties were related to lack of time and work overload, lack of knowledge, interest and training of the team to carry out the processes and the lack of incentive on the part of the management to implement the systematization. It is concluded that, for the challenges to be overcome, there must be a collective construction between theory, practice and management, so that the processes are reorganized and reflect on the provision of a more scientific, comprehensive, individualized and qualified assistance for the mother binomial and son.